2018
DOI: 10.1080/20008198.2018.1472991
|View full text |Cite
|
Sign up to set email alerts
|

The enemy in the mirror: self-perception-induced stress results in dissociation of psychological and physiological responses in patients with dissociative disorder

Abstract: Background: Patients suffering from dissociative disorders (DD) are characterized by an avoidance of aversive stimuli. Clinical experience has shown that DD patients typically avoid the confrontation with their own faces in a mirror (CFM). Objective: To investigate potential CFM-associated self-reported and psychophysiological stress reactions of DD patients, which most likely inform on the still unknown pathophysiology of dysfunctional self-perception in DD. Method: Eighteen DD patients and 18 healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 82 publications
(115 reference statements)
0
25
0
Order By: Relevance
“…Those authors found a significant increase in IAc linked to facial mirror-confrontation in healthy participants. Since mirror-confrontation with their faces has proven to be associated with stress and state dissociation in the sDID patient sample of the present investigation ( Schäflein et al, 2016 , 2018 ), increased self-focus by facial mirror-confrontation might have resulted in an increase in IAc, whereas the simultaneous stress and state dissociation experience might have diminished IAc. Fairclough and Goodwin (2007) , for instance, have shown an IAc decrease associated with stress in healthy women.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Those authors found a significant increase in IAc linked to facial mirror-confrontation in healthy participants. Since mirror-confrontation with their faces has proven to be associated with stress and state dissociation in the sDID patient sample of the present investigation ( Schäflein et al, 2016 , 2018 ), increased self-focus by facial mirror-confrontation might have resulted in an increase in IAc, whereas the simultaneous stress and state dissociation experience might have diminished IAc. Fairclough and Goodwin (2007) , for instance, have shown an IAc decrease associated with stress in healthy women.…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, Pollatos et al (2016) found that in Anorexia Nervosa patients, interoceptive accuracy was higher when focusing on another person’s face than when being confronted with their own faces, whereas the opposite was the case for healthy controls. We have recently shown altered self-perception in the sDID patient sample of the present investigation: mirror-confrontation with their own faces constituted a serious stressor for them regarding self-reported stress and state dissociation, whereas healthy controls did not exhibit these stress reactions ( Schäflein et al, 2016 , 2018 ). The effect of facial mirror-confrontation on IAc has not been experimentally reproduced in sDID/DID patients.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Results investigating electrodermal activity and antidepressants have shown mixed results: some found no correlations between them, whereas others found reduction in electrodermal activity in subjects taking medications (Sarchiapone et al, 2018). Otherwise, dissociative symptoms can also influence the autonomic nervous system (Pick, Mellers, & Goldstein, s. d.;Schäflein, Sattel, Schmidt, & Sack, 2018), and are known to be frequently associated with PNES (Reuber et al, 2011;Roberts & Reuber, 2014). Dissociative symptoms were not evaluated in the present study, but should be considered in future studies.…”
Section: Limitationsmentioning
confidence: 59%
“…Such work could help solidify the empirical foundation of the ST model (or models like it), for example, by employing experimental designs in controlled environments to explore the characteristics of such states and examine the extent to which they are indeed composed of typical cohesive components, and indeed experienced as distinct from other states. Such research could utilize a variety of measures that go beyond self-reports, and include psychophysiological (Schäflein, Sattel, Schmidt, & Sack, 2018), neuroimaging (e.g., Longe et al, 2010), and implicit measures (Han, Olson, & Fazio, 2006). What is crucial, in our view, is that future study of dynamic personality models should take into account individuals' phenomenology, and particularly, attend to the way individuals experience themselves as comprised of multiple individualized parts.…”
Section: Broader Considerationsmentioning
confidence: 99%